Pengembangan Website Sebagai Peningkatan Penyebaran Informasi di Era Digital di Raudhatul Athfal (RA) Cahaya Insani Sidoarjo - Astuti, Cindy Cahyaning; Yusrinda, Rahma; Al Qur’ani, Adisti; Untari, Rahmania Sri (JRCE (Journal of Research on Community Engagement), 2025)
RA Cahaya Insani Sukodono faces the problem of a lack of students due to limited funds for promotion and the lack of innovation in school promotion efforts. This study aims to develop the official website of RA Cahaya Insani Sukodono as a more effective medium for disseminating information and promoting the school. In the current digital era, RA Cahaya Insani needs a more efficient way to spread information, as traditional media such as pamphlets and brochures have limitations. Using the SDLC model with a waterfall approach, the development of this website involves several steps, such as requirements analysis, system design, implementation, testing, and maintenance. The resulting website is designed to provide key information such as the school profile, activities, photo gallery, and online registration, while ensuring user-friendly features, an attractive appearance, and simple navigation. It is hoped that this website will enhance the school's image and provide easier access to information for teachers, parents, and the general public, while addressing the challenges in information dissemination and promotion previously faced by the school.